BALANIPA KINGDOM SYSTEM IN POLEWALI MANDAR PERSPECTIVE SIYASAH DUSTURIA - Muh Arfan; Budiarti; Sastrawati, Nila (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2024)
The aim of this research is to reveal the historical facts of the values ​​and culture of the Balanipa kingdom. The unique characteristics of the kingdom, which combines the concepts of democracy and deliberation, are a special attraction. These values ​​are related to religiosity, community, regional culture and traditions, the system of government, and the concept of Siyasah Syar’iyyah. The method used in this research is a qualitative field research with a historical approach and tries to reveal how the system of the Balanipa Kingdom in Polewali Mandar was mainly from the Siyasah Syar’iyyah Perspective. This research was conducted by collecting a number of data obtained from informants in the field to find various facts or social phenomena, then the author will analyze it and try to formulate theoretically based on what is observed. In conducting field research, observations, documentation and interviews were carried out. Data from literature studies and field study results are displayed as research findings, abstracted to obtain complete information, and interpreted to produce knowledge for drawing conclusions. The results of this study are evidence of the historical acculturation value of the royal government system and democracy as the system of government of the Republic of Indonesia. In general, it can be concluded that the concept of miniature Indonesia has been implemented by the Balanipa Kingdom.